(untitled) (Research, Society and Development, 2024)
The Visiting Professor Program Abroad is maintained by Coordination for the Improvement of Higher Education Personnel. (CAPES) and offers internship scholarships in various countries to researchers from Brazilian educational and research institutions. This study aims to assess how much the international insertion of scientific production of scholarship researchers was enhanced after the internship. To achieve this, it analyzes the profile of researchers, scientific production, and international collaboration (co-authorship with foreign researchers) through bibliometric and scientometric indicators. Data collection of scholarship researchers was conducted through CAPES and CNPq systems and refers to scholars awarded for 12 months by the Program, from 2009 to 2014, who undertook internships in countries that hosted more than 30 scholars (totaling 719 researchers and 8 countries). The scientific production of scholarship researchers was obtained by Lattes Curriculum and Web of Science. Scholarship researchers were mostly above 36 years old, with the majority undertaking internships in the United States, and the Humanities being the most benefited major area. Scholarship researchers from major areas such as Agricultural Sciences, Biological Sciences, Health Sciences, Exact and Earth Sciences, and Engineering already had a robust international insertion in the Pre-Internship period abroad, which was significantly increased after the internship abroad.